Excess Properties and Theoretical Evaluation on Ternary Systems of 1-Pentanol in n-Hexane Solution with some Organic Compounds at 313 K Using Ultrasonic Technique - Ibrahim, P.S. Syed; Jeyakumar, J. Edward; vinayagam, S. Chidambara (Journal of Applied Solution Chemistry and Modeling, 2021)
The parameters like density(ρ), ultrasonic velocity (U), and viscosity (η) were experimentally measured. The excess parameters like adiabatic compressibility, acoustic impedance, free volume, free length, internal pressure and ultrasonic velocity in addition to K value were computed from the experimental data. The variation of these parameters at a constant temperature for the three ternary systems, namely OMP + 1-pentanol+n-hexane, N, N-DMF + 1-pentanol+n-hexane, and MMP + 1-pentanol+n-hexane, have been discussed in the light of molecular interaction. Further, certain theoretical studies are validated with respect to experimental velocities, and the Chi-square test for the goodness of fit is also applied to check the validity of such theoretical models.